The major cerebral arteries proximal to the Circle of Willis contribute to cerebrovascular resistance in humans. Issue 8 (August 2016) - Warnert, Esther AH; Hart, Emma C; Hall, Judith E; Murphy, Kevin; Wise, Richard G
Cerebral autoregulation ensures constant cerebral blood flow during periods of increased blood pressure by increasing cerebrovascular resistance. However, whether this increase in resistance occurs at the level of major cerebral arteries as well as at the level of smaller pial arterioles is still unknown in humans. Here, we measure cerebral arterial compliance, a measure that is inversely related to cerebrovascular resistance, with our novel non-invasive magnetic resonance imaging-based measurement, which employs short inversion time pulsed arterial spin labelling to map arterial blood volume at different phases of the cardiac cycle. We investigate the differential response of the cerebrovasculature during post exercise ischemia (a stimulus which leads to increased cerebrovascular resistance because of increases in blood pressure and sympathetic outflow). During post exercise ischemia in eight normotensive men (30.4 ± 6.4 years), cerebral arterial compliance decreased in the major cerebral arteries at the level of and below the Circle of Willis, while no changes were measured in arteries above the Circle of Willis. The reduction in arterial compliance manifested as a reduction in the arterial blood volume during systole. This study provides the first evidence that in humans the major cerebral arteries may play an important role in increasing cerebrovascular resistance.